Polypoidal Intestinal Metaplasia and Dysplasia of the External Urethral Meatus - Mary Mathew; Bhavna Nayal; Lakshmi Rao; Raghunath Narayanan Unni; Joseph Thomas (Case Reports in Nephrology)
Urethral mucosa with intestinal metaplasia and dysplasia is a rare occurrence. To date only a single case has been reported in a male with long-standing urethral stricture. We present a 33-year-old female with polypoid intestinal metaplasia and dysplasia of the external urethral meatus in the absence of an inciting factor. Intestinal metaplasia of the urethral mucosa may undergo dysplasia, emphasizing the necessity of a high degree of clinical suspicion and vigilant pathological examination of these lesions.